PAD Cluster: An Open, Modular and Low Cost High Performance Computing System - Bernal, Volnys Borges; Kofuji, Sergio Takeo; Sipahi, Guilherme Matos; Anderson, Allan G.; Lobo Netto, Marcio (Anais do International Symposium on Computer Architecture and High Performance Computing (SBAC-PAD); 1999: Anais do XI Symposium on Computer Architecture and High Performance Computing, 1999)
This work presents the PAD Cluster, the result of PAD Elebra Project. lt was built on COTS (commodity off-the shelf) components. lt is shown the hardware and software architecture of the cluster. Some performance results are presented in the implementation of an user level communication library. Cluster management tools for a single point of control are also presented.